PENYIDIKAN TINDAK PIDANA PENYALAHGUNAAN SENJATA API YANG DILAKUKAN OLEH ANGGOTA POLISI DI RESERSE KRIMINAL UMUMKEPOLISIAN DAERAH RIAU - IRE SAPUTRA; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The investigation is a series of actions by investigators in demanding themethod set out in this law to find and collect evidence that occurred and to findthe suspect. Investigation of the police officers who are guilty is still carried outby the police themselves, even though they are subject to civil law. This raisesconcerns that the police will act arbitrarily in conducting investigations, notbased on applicable law, where police agencies try to protect their members sothat in conducting investigations no longer in accordance with applicableprocedures. So that members of the police who have been proven to havecommitted crimes can be free just because they are not dealt with properly.In the case of the police there is still reluctance to investigate eachother, and this does not rule out the possibility of collusion in the process ofinvestigating cases that cause the investigation to end with the conclusion that thepolice officers or members were not proven guilty. In the case of conducting aninvestigation into the crime of misuse of firearms carried out by members of thepolice at the General Criminal Investigation of Riau Regional Police, it has notbeen carried out properly. Investigation of the police officers who are guilty isstill carried out by the police themselves, even though they are subject to civil law.This raises concerns that the police will act arbitrarily in conductinginvestigations, not based on applicable law, where police agencies try to protecttheir members so that in conducting investigations no longer in accordance withapplicable procedures. So that members of the police who have been proven tohave committed crimes can be free just because they are not dealt with properly.The police should carry out professional investigations and inaccordance with the rules that apply and openly, do not try to hide the crime oftheir fellow members. The police in carrying out the process of carrying out theinvestigation should not view the subject who is committing a crime, even thoughthe subject is a police officer who has been a colleague in the police who canbecome an obstacle in carrying out the investigation. In the future, theinvestigation must be carried out by an independent institution that has strongauthority and position so that the investigation of criminal cases, especiallycriminal acts of misuse of firearms, is no longer covered up.